PHARMACOLOGICAL PROPERTIES OF LEONOTIS NEPETIFOLIA (L) R.BR - A SHORT REVIEW - Vasuki, *K.; priya, S. Kokila; Nandhini, P.; Pavithra, U.; Kiruthika, G. (AYUSHDHARA, 2015)
Leonotis nepetifolia (L) R.Br commonly known as Lion’s ear, has number of therapeutic properties and is also known as Christmas candlestic. The genus Leonotis has 12 species widely distributed in Pan Tropics and is represented by one species, Leonotis nepetifolia in India. It belongs to family Lamiaceae. Leonotis nepetifolia is an economically important medicinal plant of repute in Indian traditional systems of medicine such as Ayurveda, Unani and Siddha. The Ayurvedic name of the plant is Granthiparni, while the trade name is Barchi Buti. It has many therapeutic properties and proved in Madagascar, Brazil, Canada, Kenya and many African Countries to treat diseases, rheumatism, dysmenorrhoea, bronchial asthma, fever, diarrhoea influenza and malaria and is also an analgesic. The decoction of the leaves is used to treat coughs, burns and skin ailments. The whole plant is used for menstrual pain and unspecified female complaints. This plant exhibited various pharmacological activities such as antioxidant activity, antidiabetic, anticancer, anti-inflammatory, anticonvulsant, wound healing, hepatoprotective activity and antimicrobial activities. Phytochemical examination of this plant indicated the presence of alkaloids (leonurine and stachydrene), iridoid glycoside (leonuride), iridoid glycosides (leonurin and leonuridine), diterpenoids (leocardin), flavonoids (rutin, quercetin, hyperoside, apigenin), volatile oil, tannins and vitamin A. Leonotis nepetifolia is highly therapeutic and is used in various Ayurvedic formulations. This article briefly reviews the pharmacological and various therapeutic aspect of Leonotis nepetifolia.